Microplastics in an anadromous national fish, Hilsa shad Tenualosa ilisha from the Bay of Bengal, Bangladesh - Siddique, Mohammad Abdul Momin; Uddin, Azad; Rahman, Shahriar Md Arifur; Rahman, Mahfuzur; Islam, Md Sahedul; Kibria, Golam (Marine pollution bulletin, 2022)
Hilsa shad is one of the most important fisheries, contributing about 12.9% of the country's (Bangladesh) total fish production. There was no previous study on microplastic contamination of this important commercial fish. This study aims to identify, classify, and quantify microplastics (MPs) ingested by the national fish of Bangladesh, Hilsa shad, Tenualosa ilisha. A total of 287 MPs were recovered from the gastrointestinal tracts. All the fishes analyzed were contaminated with MPs. The mean (±SD) of the number of MPs was 19.13 ± 10.77 particles/fish, ranging from 7 to 51 particles/fish. Significant correlation was not found between the fish body length and MP abundance (rs = 0.287, p = 0.299), and between the fish body weight and MPs abundance (rs = 0.261, p = 0.347). The most dominant color was transparent (30%), followed by gray and black, contributing to 26% and 23%, respectively. The maximum number of MPs accounted for in the 300-1500 μm size class where fiber was the most dominant (50%) shape of observed MPs. These results provide a baseline of MP contamination in seafood from Bangladesh that should be useful for future monitoring efforts. The present study is the first research on MP contamination of Hilsa shad.
Keywords: monitorování životního prostředí; potrava z moře (živočišná); mikroplasty; Bangladéš; Bays; Environmental Monitoring; Migratory fish; zátoky; chemické látky znečišťující vodu; Plastics; Microplastics; Water Pollutants, Chemical; Seafood; zvířata; Lower Meghna River estuary; Fishes; plastické hmoty; Microplastic contamination; ryby; Bangladesh; Tenualosa ilisha; Health risk; Animals